Aminoalkylmethacrylate copolymer E improves oral bioavailability of YM466 by suppressing drug–bile interaction. Issue 9 (4th March 2013) - Takemura, Shigeo; Kondo, Hiromu; Watanabe, Shunsuke; Sako, Kazuhiro; Ogawara, Ken‐ichi; Higaki, Kazutaka; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract The aim of this study was to find out polymeric compounds that can inhibit the interaction between YM466, a novel anticoagulant, and bile to improve its oral bioavailability. In vitro ultrafiltration method using extract gall powder was useful to detect the formation of insoluble complex of YM466 with bile and also used to select a polymer that can inhibit the interaction between YM466 and bile. The in vitro studies revealed that aminoalkylmethacrylate (AAM) copolymer E, a polymethacrylate, dose‐dependently inhibited the interaction between YM466 and bile and that this polymer could interact with bile salt, but not with YM466, possibly by electrostatic and/or hydrophobic interactions. The coadministration of AAM copolymer E with YM466 to rats dose‐dependently increased the plasma concentration of YM466 and it was found that the oral dose of the polymer three times of YM466 (polymer to drug ratio in weight, P–D ratio, 3) significantly increased AUC0–1 h of YM466 to 2.6‐fold of that of YM466 alone. Considering the condition of therapeutic use of YM466 and the maximum tolerated dose of the polymer, the formulation of P–D ratio 3 would be clinically practical and promising from the viewpoint of safety. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3128–3135, 2013